Prevalence of abnormal cervical cytology on liquid-based cytology in women attending gynecology OPD at Bangalore, Karnataka, India - R., Savithri D.; J., Sankalpa A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer ranks fourth among all malignancies and it is the most common gynecological cancer in women worldwide. In India, cancer cervix is the most common gynecological cancer and accounts for about 1.8 per 100000 populations. Precancerous lesion of cervix precedes carcinoma cervix and can be picked up on cytology. Cervical cytology has proven itself to be the main weapon of defense against this disease and is been in use since 50 years. Objectives of this study are to determine the socio-demographic characteristics of the women who had cervical cytology and to determine the prevalence of abnormal cervical smears on liquid-based cytology among women attending gynecology OPD at KIMS hospital and Research Centre. Methods: This was a prospective observational study conducted at the Department of Obstetrics and Gynecology, KIMS Hospital and Research Centre. All data about the patient were recorded in a predetermined proforma. The cervical smear sample was collected using an endocervical brush and then immersed in a thin prep solution and was sent to cytopathology lab, Department of Pathology, KIMS Hospital and Research Centre for further processing using the EZIPREP technique. Results: The study included 100 cervical smears in total. Females ranged in age from 21 to 65 years. All cervical smears were evaluated. The current study found inflammatory smears, infectious and smears with epithelial cell abnormalities. The most common organism noted was Candida albicans. The age group with the highest prevalence of epithelial cell abnormality was 41-50years. The most common epithelial cell abnormality in the present study is Low grade squamous intraepithelial lesion. Conclusions: Out of the 100 LBC smears studied, the majority (67) of the smears studied were inflammatory. Epithelial cell abnormalities were found in 4 cases and the most common age group of epithelial abnormalities was the fifth decade.